A facile way to achieve all-photonic logic functions and photo-printing based on a donor–acceptor Stenhouse adduct. (20th June 2017) - Tang, Fei-Ying; Hou, Jia-Nan; Liang, Kai-Xin; Liu, Ying; Deng, Liu; Liu, You-Nian
Abstract : A small bi-photochromic molecule containing donor–acceptor Stenhouse adduct moiety and azobenzene moiety was synthesized. Its photochromic and fluorescent properties were studied. Based on its unique characteristics, all photonic logic functions and photo-printing were achieved. Abstract : Herein, a simple bi-photochromic molecule containing a donor–acceptor Stenhouse adduct and azobenzene moiety was synthesized. It can achieve all-photonic multimolecular logic functions and photo-printing. This molecule could provide a novel platform for exploring multifunctional molecular logic devices.